UNDERSTANDING ALEXITHYMIA: A REVIEW OF PSYCHOSOCIAL PERSPECTIVE - Jahangir, Memoona; Ali, Amena Zehra (Journal of Pakistan Psychiatric Society, 2024)
Objective: The objective of the review is to understand the multifaceted construct of alexithymia and its association with psychosocial variables. Method: A thorough examination of the literature on the construct of alexithymia was conducted, encompassing studies published over several years. The empirical findings over the years regarding various psychosocial variables, including attachment styles and empathy, were also reviewed. The Sociodemographic characteristics and comorbidity of alexithymia with other mental health conditions were also analyzed. Results: The review revealed that attachment bond plays a significant role in the development of alexithymia, childhood trauma because of unhealthy mother-infant bond can be one of the reasons for difficulty in understanding emotions, which leads to difficulties in empathy as well. Furthermore, alexithymia has been found to be comorbid with depression, anxiety, autism, and other mental illnesses. Conclusion: The findings of the review suggest that alexithymia is an important construct which can influence various psychosocial aspects of life. Although some of the variables have been extensively studied, much remains to be unclear. Further research will add up value to comprehensively evaluating the impact of alexithymia on psychosocial aspects. Keywords: alexithymia, psychosocial perspective, attachment styles, empathy.